The corrosion of duplex Stainless steels : a practical guide for engineers - Francis, Roger (Engineer)
In this book, Roger Francis reviews various duplex alloy compositions, mechanical properties, and design stresses for vessels and pipes to various codes. He also covers the basics of welding duplex alloys, both to themselves and to other alloys, and their corrosion resistance. Of most importance, the book looks at a variety of types of corrosion that may affect DSSs in service, presenting the available data and, in some cases, how to avoid problems.
Keywords: Stainless steel.; Duplex stainless steel.; elektronické knihy; electronic books